2023
DOI: 10.3390/ani14010121
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Protein Levels on Sheep Gut Metabolite Profiles during the Lactating Stage

Sikandar Ali,
Xiaojun Ni,
Muhammad Khan
et al.

Abstract: Diet-associated characteristics such as dietary protein levels can modulate the gut’s primary or secondary metabolites, leading to effects on the productive performance and overall health of animals. Whereas fecal metabolite changes are closely associated with gut metabolome, this study aimed to see changes in the rumen metabolite profile of lactating ewes fed different dietary protein levels. For this, eighteen lactating ewes (approximately 2 years old, averaging 38.52 ± 1.57 kg in their initial body weight) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…Other than the ingredient proportion effect, the available CP protein could affect the consistency trend. Ali et al (2023) reported the available CP can cause differences in alteration which agreed with the resent result cases. The CP sources in the present study were wheat straw, wheat bran, Noug seed cake and sainfoin hay.…”
Section: Discussionsupporting
confidence: 77%
“…Other than the ingredient proportion effect, the available CP protein could affect the consistency trend. Ali et al (2023) reported the available CP can cause differences in alteration which agreed with the resent result cases. The CP sources in the present study were wheat straw, wheat bran, Noug seed cake and sainfoin hay.…”
Section: Discussionsupporting
confidence: 77%